The validity of utilizing karate in youth safety education - Piepiora, Paweł Adam; Gwardyński, Robert (Frontiers in Sports and Active Living, 2024)
This article aims to present a new argument on the validity of utilizing karate in youth safety education. First, the important role of safety education and the need to seek new means of influencing young people is presented and the significant role of sport in this area. The field of Far Eastern combat sports was underlined here as being particularly important because they contain internal codes of moral conduct. Therefore, the new argument is to take the perspective of karate as a combat sport, martial art, and self defence system in one. Karate as a combat sport refers to fighting skills in the following directions: traditional, sport and Olympic; and in the following systems: semi contact, knockdown, full contact, mix fighting. Karate as a martial art has a health-promoting character and emphasises the psycho-physical development of practitioners and the recognition of ethical codes. And karate as a self defence system is concerned with proficiency in out-of-sport confrontations, but also in risk assessment. Karate has been found to be an effective means in educating young people to safety, but in order for it to be effective, it needs to be adopted in its entirety. Because the combat sport perspective activates youth in physical culture, the martial art perspective educates according to norms and rules; and the self defence system perspective teaches how to act in difficult situations.